Analisis Perlindungan Hukum terhadap Konsumen Pengguna Jasa Ojek Online di Kota Batam - Alfis Setyawan Setyawan; Deeky Agus Sufandy (Journal of Judicial Review, 2018)
The development of today's advanced and sophisticated communications technology also provides changes in the field of transportation with the utilization of applications to facilitate the ordering. Ojek transport online is currently growing rapidly in major cities in Indonesia including Batam City due to the convenience or practicality provided in various services that continue to be innovated by service providers tailored to the needs of service users. This research was conducted by using normative-empirical law research method. Normative-empirical legal research uses secondary data and also adds primary data. Secondary data in this research is data obtained from library materials and primary data obtained from the source of ojek online application company in Batam (Go-Jek Batam City). The data have been analyzed using qualitative descriptive method. The result of this research is the legal relationship between the consumer as the user of the ojek transportation service online with the business actor form of an electronic agreement, the legal responsibility of the online motorcycle company relates to the presumption based responsibility, while the legal responsibility of the motorcycle driver online is related to the principle of responsibility based on the element of mistake and the principle of presumption to always be responsible, the legal protection of the consumer as the user of the transportation service ojek online in Batam City by providing protection for its consumers in terms of security, safety and comfort and protection of the rights of victims (consumers of service users).